Rhinoglotophilia and the affirmation grunt: a universal tendency - Parker, Steve (2006)
Rhinoglottophilia and the affirmation grunt- a universal tendency. Based on a corpus of 705 attested words far 'yes' collected from 582 languages spoken in 74 countries, I propose a basic universal template or canonical form for this lexical item having the pattern /he?e/. In the accompanying discussion I suggest a formal and functional explanation for this phenomenon by appealing to the notion of minimal articulatory gesture.